Chromosome disorders: chromosomes intro and tool-kit - Holden, Simon (Henry Stewart Talks, 2019)
Normal and abnormal chromosome structure, Balanced and unbalanced chromosomes, ISCN chromosome nomenclature, Chromosome imbalances and ‘genomic’ disorders, Common chromosome rearrangements, Methods of testing for chromosome disorders